Effects of medicated and non-medicated urea molasses multi-nutrient block supplements on intake, digestibility and performance of lactating saanen goats fed on conventional diets - Mira Panadi (2018)
The objectives of this study were to evaluate the nutritional composition of urea molasses multi-nutrient block (UMMB), medicated UMMB (MUMB) and commercial mineral block (CMB) and their effects on the performance of lactating Saanen goats in term of feed intake, milk yield, body weight changes, body condition score (BCS), blood profiling, parasite infestation and nutrient digestibility. A trial was conducted at a smallholder farm in Kemahang, Tanah Merah, Kelantan for 90 days of feeding trial and seven (7) days for digestibility trial. Twenty four (24) lactating Saanen goats (with mean initial body weight: 40.1 kg; average milk yield < 1 litre/d) were randomly assigned to four groups with six (6) goats each, based on randomized complete block design (RCBD). Four dietary treatments were evaluated, i.e. T1- fed on a basal diet which consisted of 3 kg roughages and 1 kg commercial goat pellet (control group). The goats in T2, T3 and T4 received equal amounts of basal diet with supplementation of UMMB, MUMB and CMB respectively. The effect of supplementation on faecal egg count (FEC) and nutrient digestibility were also studied. Crude protein (CP) and ether extract (EE) contents in UMMB and MUMB were 33.84% and 0.55%; and 32.84% and 0.82% respectively. Over 90 days of the feeding trial, total dry matter intake (DMI) (kg/d) in T2 (1.29) and T3 (1.25) were significantly higher (p<0.05) than those in T1 (1.14) and T4 (1.16). Milk yield (L/d) was significantly higher (p<0.05) in T2 (1.55), followed by T3 (1.34), T4 (0.98) and T1 (0.79). Highest average of daily gain (ADG) (g/d) were recorded in T2 (53.6) followed by T3 (45.6), T4 (39.7) and T1 (37.7). There were no significant differences (p>0.05) between treatments on body weight changes and BCS while blood profiling was significantly differed (p<0.05) between treatments. Serum concentrations of Ca, Fe, Cu and Zn were highest in T2 with the values of 33.6±0.6 ppm, 341.7 ppb, 270.03 ppb and 138.3 ppb respectively as compared to other treatments. The goats in T2 and T3 showed moderate levels of parasite infestation with FEC (epg) of 750 and 950 respectively as compared to 4917 and 1850 in T1 and T4 respectively. The digestibility of DM and CP were significantly higher (p<0.05) in T2 and T3 with the values of 79.4% and 80.2% and 77.2% and 75.2% respectively. Overall, UMMB and MUMB supplementation can be considered to have beneficial effects over CMB in increasing feed intake, milk yield and body weight gain of the lactating goats, apart from enhancing their dry matter and crude protein digestibility.